Opposing Effects of TGFβ and BMP in the Pulmonary Vasculature in Congenital Diaphragmatic Hernia - Mous, Daphne S.; Buscop-van Kempen, Marjon J.; Wijnen, Rene M. H.; Tibboel, Dick; Morty, Rory E.; Rottier, Robbert J. (Frontiers in Medicine, 2021)
Background: Pulmonary hypertension is the major cause of morbidity and mortality in congenital diaphragmatic hernia (CDH). Mutations in several genes that encode signaling molecules of the transforming growth factor β (TGFβ) and bone morphogenetic protein (BMP) pathways have previously been associated with CDH. Since studies on the activation of these pathways in CDH are scarce, and have yielded inconsistent conclusions, the downstream activity of both pathways was assessed in the nitrofen-CDH rat model. Methods and Results: Pregnant Sprague-Dawley rats were treated with nitrofen at embryonic day (E) 9.5 to induce CDH in offspring. At E21, lungs were screened for the expression of key factors of both signaling pathways, at both the mRNA transcript and protein levels. Subsequently, paying particular attention to the pulmonary vasculature, increased phosphorylation of SMAD2, and decreased phosphorylation of Smad5 was noted in the muscular walls of small pulmonary vessels, by immunohistochemistry. This was accompanied by increased proliferation of constituent cells of the smooth muscle layer of these vessels. Conclusions: Increased activation of the TGFβ pathway and decreased activation of the BMP pathway in the pulmonary vasculature of rats with experimentally-induced CDH, suggesting that the deregulated of these important signaling pathways may underlie the development of pulmonary hypertension in CDH.